DO CHANGES IN ANAL SPHINCTER ANATOMY CORRELATE WITH ANAL FUNCTION IN WOMEN WITH A HISTORY OF VAGINAL DELIVERY? - MURAD-REGADAS,Sthela Maria (2014)
Objectives To evaluate anal sphincter anatomy using three-dimensional ultrasonography (3-DAUS) in incontinent women with vaginal delivery, correlate anatomical findings with symptoms of fecal incontinence and determine the effect of vaginal delivery on anal canal anatomy and function. Methods Female with fecal incontinence and vaginal delivery were assessed with Wexner’s score, manometry, and 3DAUS. A control group comprising asymptomatic nulliparous was included. Anal pressure, the angle of the defect and length of the external anal sphincter (EAS), the anterior and posterior internal anal sphincter (IAS), the EAS + puborectal and the gap were measured and correlated with score. Results Of the 62, 49 had fecal incontinence and 13 were asymptomatic. Twenty five had EAS defects, 8 had combined EAS+IAS defects, 16 had intact sphincters and continence scores were similar. Subjects with sphincter defects had a shorter anterior EAS, IAS and longer gap than women without defects. Those with a vaginal delivery and intact sphincters had a shorter anterior EAS and longer gap than nulliparous. We found correlations between resting pressure and anterior EAS and IAS length in patients with defects. Conclusions Avaliar a anatomia do esfíncter anal usando ultra-sonografia tridimensional (3D-US) em mulheres incontinentes com parto vaginal, correlacionar os achados anatômicos com sintomas de incontinência fecal e, determinar o efeito do parto vaginal sobre a anatomia e função do canal anal.